Damage detection in submerged plates using ultrasonic guided waves - Sharma, S.; Mukherjee, Abhijit (Indian Academy of Sciences, 2014)
This paper describes a non-contact and non-invasive health monitoring strategy for submerged plate structures using guided waves. The structure under consideration is immersed in water and subjected to longitudinal ultrasonic waves at specific angles of incidence using a cylindrical piezoelectric transducer using the surrounding water as coupling medium. Suitable ultrasonic guided wave modes with optimum scanning capabilities have been generated and identified in submerged plate system. Finally, the propagation of selected modes through submerged notched plates is investigated. Sensitivity of leaky waves to the notches has been studied. The methodology would help in identifying damages in the submerged plate structures.